2014
DOI: 10.1175/jamc-d-12-0337.1
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Motion Vectors from Model Simulations. Part II: Interpretation as Spatial and Vertical Averages of Wind and Role of Clouds

Abstract: This is the second part of a two-part paper whose main objective is to improve the characterization of atmospheric motion vectors (AMVs) and their errors to guide developments in the use of AMVs in numerical weather prediction (NWP). AMVs tend to exhibit considerable systematic and random errors. These errors can arise in the AMV derivation or the interpretation of AMVs as single-level point estimates of wind. An important difficulty in the study of AMV errors is the scarcity of collocated observations of clou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…It has been shown that, when the height‐assignment error is small, the tracking error, estimated using observation‐minus‐background statistics, from the ECMWF and Met Office systems ranges from 2–3 m s −1 (Lean et al ). The height‐assignment error has been estimated by Folger and Weissmann (), Hernandez‐Carrascal and Bormann (), Lean et al () and Salonen et al () using the technique of best‐fit statistics . The errors have been quantified within a range of 50–150 hPa.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that, when the height‐assignment error is small, the tracking error, estimated using observation‐minus‐background statistics, from the ECMWF and Met Office systems ranges from 2–3 m s −1 (Lean et al ). The height‐assignment error has been estimated by Folger and Weissmann (), Hernandez‐Carrascal and Bormann (), Lean et al () and Salonen et al () using the technique of best‐fit statistics . The errors have been quantified within a range of 50–150 hPa.…”
Section: Introductionmentioning
confidence: 99%
“…The realism and robustness of the resulting uncertainty estimates depend on the realism and representativeness of the reference dataset. This work builds upon the work of Bormann et al (2014) and Hernandez-Carrascal and Bormann (2014), who showed that wind tracking could be divided into distinct geophysical regimes by clustering by cloud conditions. This study supplements that approach with the addition of machine learning, which, compared with traditional linear modeling approaches, should allow the model to capture more complex non-linear processes in the error function.…”
mentioning
confidence: 89%
“…A reliable estimate of the magnitude of the height-assignment error is critical for NWP data assimilation and must be accounted for [69]. Numerous studies have also been done to investigate the interpretation and impact of interpreting satellite winds as a layer-average wind [64,68,[70][71]. The stereo method enables the retrieval of very accurate cloud heights, and therefore, very accurate satellite wind height assignments; and therefore, we expect potential for the stereo winds to contribute to improving the skill of NWP forecasts.…”
Section: Orographic Cloud Effectsmentioning
confidence: 99%